Pengaruh Lingkungan Kerja Fisik Dan Tim Kerja Terhadap Prestasi Kerja Karyawan Pada CV Agung Mandiri Motor - Romana Agnesia Asti Langga; Maria Silvana Mariabel Carcia; Walter Obon (Jurnal CUAN Universitas Nusa Nipa Maumere, 2023)
This study aimed to: (1) determine the description of the physical work environment and work team on work performance (2) analyze the physical work environment and work team on work performance both partially and simultaneously. The population in this study was 30 employee participants at Cv Agung Mandiri Motor Maumere. Since the population was limited, this research was conducted by census or saturated sampling. Data were collected through questionnaires and analyzed using descriptive and inferential statistical methods. namely multiple linear regression. Hypothesis testing was done through the F-test and 1- test. The results of descriptive analysis showed that the variables of Work Achievement, Physical Work Environment, and Work Team were categorized as good. The results of the t-test statistics showed that partially the Work Environment variable had a positive and insignificant effect on Work Performance while the Work Team had a positive and significant effect on Work Performance. The statistical results of the F test showed that simultaneously all independent variables had a significant effect on Work Performance. The results of the determination analysis indicated that the two independent variables in this study were able to explain the variation in the rise and fall of Work Performance by 50%.